DEVELOPMENT OF FASHIONABLE WHEELCHAIRS FOR MOTORICALLY DISABLED PEOPLE - Siti Farida; Asrorul Mais; Lailil Aflahkul Yaum (Pusat Studi Difabilitas (PSD) LPPM Universitas Sebelas Maret, 2023)
This research aims to develop fashionable wheelchairs so that they are qualified to be properly utilized by motorically disabled people for conventional use or during fashion shows or national and international fashion carnivals. A vast mobile ability in every aspect of life has become a dream for many people, especially those with special needs. Amidst the difficulties faced by the physically disabled, disabled college students desire to drive from their homes to campuses or anywhere else. This research is a developmental research. The model of development implemented is ADDIE (Analyze, Design, Development, Implementation, Evaluation). After the production stage, the early prototypes will then be validated by an expert in teaching-learning media. The data obtained in this research are from interviews and observations from the subjects, which are motorically disabled college students. The instruments for data collection are in the forms of interviews and observations. Based on the goal of the development of product design, this product reached the success rate of 100% with the qualification of feasible usage, while in terms of manual book it reached the success rate of 80%. Moreover, the success rate of tutorial videos reached 95% with the qualification of feasible usage. The success rate as of the publication of this article was as much as 80% because the results for stage 2 of product test was pending. The assessment given for this product received a success rate of 100% with the qualification of feasible usage due to the products developed in partnership with manufacturing experts and the production site where the products are made by adjusting the conditions and needs of students with motor disabilities. In this aspect of the assessment, the media expert gave advice to pay attention to the materials and the manufacturing process. Therefore, these fashionable wheelchairs can acquire the classification of feasible usage by the motorically disabled for conventional use or for fashion shows or national or international fashion carnivals